Analysis Of Digital Marketing Strategies At Bank Negara Indonesia (Bni) Sumedang Branch Office - Sugiharti, Elis; Puspasari, Dewi; Damayanti, Wulan Ariani (SINTESA, 2024)
A digital marketing strategy is a strategy that uses online marketing in its marketing activities or promotion of a brand or product which is certainly very profitable because it can attract consumers and potential consumers quickly. This research analyzes the focus of implementation. obstacles, and how to overcome digital marketing obstacles at Bank Negara Indonesia (BNI) Sumedang Branch Office. The aim of this research is to determine the implementation of digital marketing at Bank Negara Indonesia (BNI) Sumedang Branch Office. The approach method used in this research is the qualitative research method. The sampling technique was carried out using a proportional sampling technique, the informants were the marketing and business unit leaders of Bank BNI KC Sumedang, 2 priority customers and 13 regular customers. The data validity test is a triangulation technique. Digital Marketing at Bank Negara Indonesia (BNI) Sumedang Branch Office includes Websites (Static Websites & Dynamic Websites), Search Engines or search engines (SEO&SEM), Social Media Marketing (Entertainment, Interaction, Trendness, Customization, Advertisement), Mobile Marketing (Quality information, security, customer relations, responsiveness, fulfillment), and Online Advertising (Pop Up & Floathing Ads). The results of Digital Marketing research carried out at Bank BNI KC Sumedang show that the implementation of digital marketing at Bank BNI, especially Bank BNI KC Sumedang, has been carried out well from the website aspect to online advertising. Bank BNI KC Sumedang is expected to reach more remote areas in Sumedang so that Bank BNI can reach customers more widely.